Pengaruh Media Sosial Instagram dan Harga Tiket terhadap Keputusan Berkunjung Event Deliland Festival 2023 - Hutabarat, Rebekka; Saragih, Agus Mariani (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to determine the influence of Instagram social media and ticket prices on the decision to visit the Deliland Festival 2023 event partially and simultaneously. This research uses quantitative methods. The object of this research is the Deliland Festival 2023 with data collected through questionnaires and observations. This research was analyzed using data quality tests, classic assumption tests consisting of normality and reliability, multiple linear regression analysis, hypothesis testing and coefficient of determination tests. The results of this research show that partially the social media Instagram has a positive and significant influence on the decision to visit the Deliland Festival 2023 event. The ticket price partially has a positive and significant influence on the decision to visit the Deliland Festival 2023 event. Simultaneously the social media variables Instagram and the ticket price have an influence positive and significant towards the decision to visit the Deliland Festival 2023. Then based on the determination value it lies in R Square. It is known that the coefficient of determination value is R2 = 0.527, which means that all independent variables, namely social media Instagram and ticket prices, influence the decision to visit by 52.70% and the remaining 47.30% can be explained by other variables not examined in this research. Keywords: Instagram, Price, Visiting Decision.